Sustainable Performance of Industrialised Building Systems in the Construction Phase - Noor Azhar, Noor Fatin Aida; Abas, Nor Haslinda; Mohd Taat, Nurul Hasanah; Sabtu, Hilyati; Abbasi , Suhail Ahmed (International Journal of Integrated Engineering, 2024)
The Industrialised Building System (IBS) is a construction method where components are manufactured in controlled environments, either on-site or offsite, before being assembled into construction works. Over the past several decades, it has garnered growing interest as a method to promote sustainable building. This study identified sustainable indicators through literature reviews, extracting sixteen indicators for a sustainability evaluation. A survey was conducted among developers, designers, civil and structure (C&S) consultants, mechanical and electrical (M&E) consultants, manufacturers, and contractors in North Malaysia, focusing on Kedah state, to identify their perceptions on the sustainable indicator performance of IBS construction. The participants had experience in both IBS and conventional construction. The data collected from the questionnaires were analyzed for the mean and Relative Importance Index (RII). The results revealed significant changes in IBS construction compared with conventional construction across all indicators. The top three indicators were reducing the amount of formwork, labour availability, and reducing site disruption. Next, the analysis of the within-group comparison using Intra-class Correlation (ICC) of the indicators revealed that contractors, developers and manufacturers possessed moderate similarity within the same group of organisations. This research gives an overview of the present perspectives of performance of sustainable indicators across key stakeholders in the Kedah construction sector. This is especially beneficial because IBS has grown in popularity and popularity owing to its ability to enhance the building environment, quality, and productivity.